The Microbiome and Musculoskeletal Conditions of Aging: A Review of Evidence for Impact and Potential Therapeutics. (February 2016) - Steves, Claire J; Bird, Sarah; Williams, Frances MK; Spector, Tim D
ABSTRACT: Recently, we have begun to realize that the billions of microorganisms living in symbiosis with us have an influence on disease. Evidence is mounting that the alimentary tract microbiome, in particular, influences both host metabolic potential and its innate and adaptive immune system. Inflammatory states characterize many bone and joint diseases of aging. This prompts the hypothesis that the gut microbiome could alter the inflammatory state of the individual and directly influence the development of these common and burdensome clinical problems. Because the microbiome is easily modifiable, this could have major therapeutic impact. This perspective discusses evidence to date on the role of the microbiome and the highly prevalent age‐related disorders of osteoporosis, osteoarthritis, gout, rheumatoid arthritis, sarcopenia, and frailty. It also reviews data on the effects of probiotics and prebiotic interventions in animal and human models. Despite suggestive findings, research to date is not conclusive, and we identify priorities for research to substantiate and translate findings. © 2015 American Society for Bone and Mineral Research.